(untitled) (Международный научный журнал «Инженер», 2026)
The influence of the dispersion and content of ground silica gel on the properties of cement paste in the presence of a polycarboxylate-based superplasticizer was investigated. Silica gel was introduced in amounts of 5, 10, and 15% by mass of cement, while the superplasticizer dosage was 1%. It was established that an increase in the fineness of silica gel promotes the intensification of hydration processes and the formation of a denser cement paste structure. It was shown that the optimal silica gel content is 5%, at which the maximum strengthening effect is achieved. The incorporation of the superplasticizer reduces the water-to-cement ratio and enhances the compressive strength of the cement paste; however, it is accompanied by an increase in setting time. The highest strength was obtained for the composition containing 5% finely dispersed silica gel and 1% superplasticizer. The observed effect is attributed to the combined action of the additives and the densification of the cement paste structure.